Graves' Disease, Hypoparathyroidism, Systemic Lupus Erythematosus, Alopecia, and Angioedema: Autoimmune Polyglandular Syndrome Variant or Coincidence?. (January 2013) - Melcescu, E.; Kemp, E.H.; Majithia, V.; Vijayakumar, V.; Uwaifo, G.I.; Koch, C.A.
Data on coexisting Graves' disease (GD), hypoparathyroidism, and systemic lupus erythematosus (SLE) are limited. The thyroid and parathyroid glands may be extra sensitive to irradiation damage in an underlying autoimmune condition. A 34-year-old black woman presented with tetanic-like cramps, easy skin bruising, fatigue, weight gain, nocturia and back pain. She was previously diagnosed with GD in 2001 and underwent radioiodine therapy (RAI) in 9/01 using 6 mCi. PostRAI (November 2001) she developed hypocalcemia and hypothyroidism (2/02). In 2007, SLE was diagnosed. In October 2009, s-calcium and PTH were still low at 7.1 mg/dl and 9 pg/mL, respectively, although the patient denied symptoms on vitamin D and calcium supplementation. To identify possible autoimmune damage of the parathyroids, we evaluated the presence of activating antibodies to the CaSR and also analyzed the DNA sequence of all 6 translated exons and flanking intronic sequences of her CaSR gene for a functionally significant CaSR mutation but neither was positive. The initial autoimmune damage to her thyroid and possibly parathyroid glands followed by irradiation of them seems to have contributed to her developing both hypoparathyroidism (11/01) and hypothyroidism (2002). The patient could potentially have had parathyroid autoantibodies in 2001 that disappeared by 2009 when she was tested for them. We consider that the multiple autoimmune conditions developed over the past decade of her life with the concurrent irradiation contributing to her brittle hypoparathyroidism. Select patients with GD and perhaps parathyroid autoantibodies with a slowly developing destructive impact on the parathyroid glands may then develop overt hyoparathyroidism with rather low dose RAI ablation. This patient adds to the evolving spectrum of polyglandular syndrome variants.